Olga Lebedeva ( Madame Gülnar): A Russian Orientalist and Translator Enchants the Ottomans - Türkan Olcay (Slovo, 2017)
Based on the studying of a number of archive and scientific literature sources, the article attempts a research of life and works of the first Russian female orientalist Olga Sergeevna Lebedeva. Under the pseudonym ‘Gülnar’, she was one of the first to introduce the Turkish reading public to the treasures of Russian literature, thus making an invaluable contribution to Turkish–Russian literary connections at the end of the nineteenth century. A special place in the article is devoted to Olga Lebedeva’s translations and literary critical studies in the Ottoman Empire in 1890s and also interrelationship between her and the prominent Ottoman writer and publisher Ahmet Mithat Efendi. Read here.